2020
DOI: 10.3390/nano10122481
|View full text |Cite
|
Sign up to set email alerts
|

Excellent, Lightweight and Flexible Electromagnetic Interference Shielding Nanocomposites Based on Polypropylene with MnFe2O4 Spinel Ferrite Nanoparticles and Reduced Graphene Oxide

Abstract: In this work, various tunable sized spinel ferrite MnFe2O4 nanoparticles (namely MF20, MF40, MF60 and MF80) with reduced graphene oxide (RGO) were embedded in a polypropylene (PP) matrix. The particle size and structural feature of magnetic filler MnFe2O4 nanoparticles were controlled by sonochemical synthesis time 20 min, 40 min, 60 min and 80 min. As a result, the electromagnetic interference shielding characteristics of developed nanocomposites MF20-RGO-PP, MF40-RGO-PP, MF60-RGO-PP and MF80-RGO-PP were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Figure 8 a–f shows the loss tangent for all the prepared samples. The term “dielectric loss tangent” refers to the amount of electrical energy dissipated in a material as a result of several physical processes, including domain wall dielectric resonance, electrical conduction, and dielectric relaxation [ 50 , 51 ]. Following Maxwell–Wagner interfacial polarization, all samples display the same loss tangent behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 8 a–f shows the loss tangent for all the prepared samples. The term “dielectric loss tangent” refers to the amount of electrical energy dissipated in a material as a result of several physical processes, including domain wall dielectric resonance, electrical conduction, and dielectric relaxation [ 50 , 51 ]. Following Maxwell–Wagner interfacial polarization, all samples display the same loss tangent behavior.…”
Section: Resultsmentioning
confidence: 99%
“…The saturation magnetization value is 4.07 emu/g and 51.98 emu/g for ZnFe2O4 and CoFe2O4 nanoparticles, respectively. The low value of saturation magnetization of spinel ferrite nanoparticles compared with bulk is due to its small particle size [11]. Further, the value of coercivity Hc ≈ 36.17 Oe and remanent magnetization Mr 3.37emu/g, for CoFe2O4 nanoparticles revealing its ferromagnetic behavior.…”
Section: Magnetic Studymentioning
confidence: 94%
“…However, the value of SER is 22.20 dB for ZnFe2O4 -rGO-TPU and 21.99 dB for CoFe2O4 -rGO-TPU, as shown in Figure 3(c). It signifies that absorption is the major contributor to the shielding performance of ZnFe2O4 -rGO-TPU and CoFe2O4 -rGO-TPU nanocomposites [11]. The high shielding effectiveness due to absorption is attributed to the interaction of electric and magnetic dipoles.…”
Section: Magnetic Studymentioning
confidence: 97%
“…Moreover, the incorporation of rGO as a second filler along with magnetic spinel ferrites can help in the enhancement of interfacial polarization, high electrical conductivity, and good impedance matching. In our recent work, we demonstrated excellent EMI shielding with MnFe 2 O 4 and rGO in a polypropylene matrix [ 12 ]. Further, the research group of Kumar et al [ 13 ] reported total shielding effectiveness of ≈ 38.2 dB for NiFe 2 O 4 and rGO nanocomposite in the X-band frequency range.…”
Section: Introductionmentioning
confidence: 99%